Integrity Reinforcement Management in Madrasah Tsanawiyah Negeri (MTsN) 2 Tasikmalaya - Wiwin Nuraeni (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
Integrity is one character instilled into the participants of Character Education Reinforcement (Penguatan Pendidikan Karakter-PPK) policies, as mentioned in the Government Regulation Number 87 of 2017. The research revealed integrity reinforcement management in MTsN 2 Tasikmalaya. The present study employed a descriptive qualitative approach with observation, interview, and documentation to collect the data. The results showed that the management of integrity character education in MTsN included several activities. (1) Planning, conducted by the stakeholder representatives to discuss the intra-curricular activities (learning), co-curricular (enrichment), extracurricular, and counseling. (2) Organizing, conducted by the principal, committee, teachers, and staff of the madrasah. (3) Implementing the activities, treating the civic education subject as the leading sector for implementing integrity reinforcement. (4) Monitoring by the principal, vice-principal in charge of the students, and civic education and counseling teachers. The management success was supported by the surrounding environments of the madrasah, teachers, and staff (internal) and parents and society (external). Meanwhile, the program faced some obstacles from the social media and the social environment of the learners. The findings imply the need for good cooperation between the madrasah, parents, and society. Monitoring the social media and the social interaction among learners become the concerns of the stakeholders.